Model Analisis Faktor yang Mempengaruhi Keputusan Pembelian Sepeda Motor Second di Palembang - Mail Hilian Batin; Ahmad Syahrizal (Indonesian Journal of Islamic Economics and Business, 2021)
This study aims to analyze whether the price and promotion factors have an influence on the decision to purchase a second motorcycle at the Rian Motor Palembang showroom. The type of research is quantitative research with the determination of accidental sampling as many as 100 respondents. The research found that: (a) price has a positive and significant influence on the decision to purchase a second motorcycle at the Rian Motor Showroom with a significance result of 0.000 and (b) promotion also has a positive and significant effect with a significance value of 0.000. Taken together, it can be proven that price and promotion can influence the decision to buy a second-hand motorcycle at the Rian Motor Palembang showroom